Prevalence of parent-reported food allergy among children in China: A population-based cross-sectional survey - Feng, Hua; Luo, Nan; Lu, Yuanan; Lu, Justin; Zhou, Jiangdong; Xiong, Xiujuan; Chen, Zhuo; Chen, Yan; Wu, Yongning (Frontiers in Immunology, 2022)
Objective: The prevalence of food allergy (FA) has been increasing in recent years and has become an important public health, food safety and clinical nutrition problem. However, population-based studies on the prevalence of FA are very limited in China. This study aims to determine the prevalence and pattern of parent-reported FA among school children in Jiangxi Province, China. Methods: A multicenter cross-sectional study on FA was conducted on primary school children aged 6-11 years old using random cluster sampling with questionnaire survey. Parent-reported FA was used and defined as individual reported FA by parent or guardian through questionnaire in this study. Result: Among the total of 8,856 (96.36%) complete questionnaires received, 727 (8.2%) children had adverse reactions to food (ARF). The prevalence rates of parent-reported FA and doctor-diagnosed FA were 6.2% and 3.3%, respectively. Animal-derived foods were the main causative source of FA, and the three leading allergenic foods were shrimp, mango and molluscs. Skin reactions were the most common clinical manifestations of FA, accounting for 63.7%, and 45.32% of the subjects with parent-reported FA experienced severe allergic reactions. There was a significant difference in parent-reported FA between different survey centers, and FA risk increased significantly in children with other allergic diseases (P<0.001) and small family size (P=0.026); The FA prevalence was significantly higher among children aged 8-11 years than those aged 6-7 years(P=0.020). Conclusions: High prevalence of parent-reported FA was observed in children among general primary schools in Jiangxi Province, China. Shrimp, mango and molluscs were the most common causative foods. The main common symptoms of FA were the adverse reactions relating to the skin system. The rate of severe allergic reactions was also high in Jiangxi Children with reported FA. Local standards and policies for the prevention and management of FA need to be adjusted on a timely basis according to actually local conditions.